Surgical excision of the right ventricular hydatid cyst: a case report - Abanoz, Mustafa; Yazar, Mehmet; Talay, Süreyya; Mansuroglu, Candan (The European Research Journal, 2024)
Hydatid cyst is described as an endemic situation predominantly observed in different undeveloped regions of the world which is caused by Echinococcus granulosus tapeworm. This disease usually affects the lungs or liver. Cardiac location is reported in less than 2 % to 0.5% of patients in all cases and as in our case the intraventricular location is seen seldomly. A 38-year-old female patient with diagnosed systemic hydatid cyst disease was consulted with chest pain, palpitation, and shortness of breath. Transthoracic echocardiography and cardiac computerized tomography imaging showed the location of the cardiac hydatid cyst was the right ventricle. She underwent elective surgery swiftly and was discharged uneventfully.